Current Pharmacological Advances in the Treatment of Cardiac Arrest - Andry Papastylianou; S. Mentzelopoulos (Emergency Medicine International)
Cardiac arrest is defined as the sudden cessation of spontaneous ventilation and circulation. Within 15 seconds of cardiac arrest, the patient loses consciousness, electroencephalogram becomes flat after 30 seconds, pupils dilate fully after 60 seconds, and cerebral damage takes place within 90–300 seconds. It is essential to act immediately as irreversible damage can occur in a short time. Cardiopulmonary resuscitation (CPR) is an attempt to restore spontaneous circulation through a broad range of interventions which are early defibrillation, high-quality and uninterrupted chest compressions, advanced airway interventions, and pharmacological interventions. Drugs should be considered only after initial shocks have been delivered (when indicated) and chest compressions and ventilation have been started. During cardiopulmonary resuscitation, no specific drug therapy has been shown to improve survival to hospital discharge after cardiac arrest, and only few drugs have a proven benefit for short-term survival. This paper reviews current pharmacological treatment of cardiac arrest. There are three groups of drugs relevant to the management of cardiac arrest: vasopressors, antiarrhythmics, and other drugs such as sodium bicarbonate, calcium, magnesium, atropine, fibrinolytic drugs, and corticosteroids.